Implementasi Sistem Pendukung Keputusan Penentuan Calon Legislatif Dengan Menggukan Metode Simple Additive Weighting (Studi Kasus: Partai Demokrat Sumatera Utara) - Yusmei Gulow (Cattleya Darmaya Fortuna, 2021)
Information system is a very important thing in making a decision. Because the information system has a very high value, so that decisions are taken more quickly and accurately, it must be supported by relevant and accurate data capable of being used by each party in supporting the progress of the organization or company in achieving goals in making good decisions, for this reason members the title